2020
DOI: 10.12973/eu-jer.9.4.1663
|View full text |Cite
|
Sign up to set email alerts
|

Change in Knowledge and Awareness in Teacher Education on Satoyama Environmental Learning: Through a Blend of Learning Spaces, Methods and Media

Abstract: Lessons on Satoyama environmental education were held for undergraduate students who are training to be educators. The lessons blend inquiry-based learning through research using ICT tools and experiential learning in a complementary manner. Students learn about the underlying concepts about the environment from a global perspective through inquiry-based learning; experiential learning can encourage students to get involved with the environment at the local level and also develop abilities and skills to conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…All four clusters of abilities were significant for the mean increase in scores on all consciousness which belongs to each of the four ability clusters. Almost items had significant increased [13]. This means that results for scores of the consciousness which was collected into each cluster are same as result for score of each item.…”
Section: On Significance Testing Of Mean Increase In Scores Of Consci...mentioning
confidence: 73%
See 1 more Smart Citation
“…All four clusters of abilities were significant for the mean increase in scores on all consciousness which belongs to each of the four ability clusters. Almost items had significant increased [13]. This means that results for scores of the consciousness which was collected into each cluster are same as result for score of each item.…”
Section: On Significance Testing Of Mean Increase In Scores Of Consci...mentioning
confidence: 73%
“…In order to better fulfil Dubos' vision, BL which combines inquiry-based learning and experiential learning, will be the teaching methodology adopted in this study on the effect of environmental education on satoyama. Learning effects in this teacher education on satoyama environmental learning has been reported already [13]. The purpose of this paper is to know reasons that this learning shows effects by revealing activities effective for improving abilities.…”
Section: Introductionmentioning
confidence: 91%
“…It can also be seen that students in social science teacher education indicated that environmental education promotes development in its cognitive, affective and behavioral dimensions such as information and increased awareness of resource use, self-awareness and environmental sensitivity, problem solving, understanding of sustainability, positive attitudes and behavioral developments and changes that have a positive effect on an individual's level of environmental literacy. In addition, Miyaji and Fukui (2020) concluded that the average score for all subjects on trust and willingness to participate in environmental education increased. In terms of skill awareness, students feel that their skills have improved significantly in all subjects.…”
Section: • This Study Can Highlight the Most Important Findings And D...mentioning
confidence: 99%
“…Some of these studies are related to environmental awareness and attitudes toward the environment. Many studies investigating attitudes towards the environment showed that most of the participants develop positive attitudes toward environment (Adanali & Mete, 2019;Dolenc Orbanic & Kovac, 2021;Durmus & Kinaci, 2021;Miyaji & Fukui, 2020;Molefe & Aubin, 2021;Ozonur, 2021;Shagiakhmetova et al, 2022;Zhdanov et al, 2022). Some studies have investigated the relationship between environmental education and some variables that may be related to it.…”
Section: Introductionmentioning
confidence: 99%
“…The check was done so that the data used was truly 'selected' and suitable for use. At this stage, the researcher conducted an interpretation stage (Miyaji & Fukui, 2020;Bobrytska et al, 2020), as a final stage of data analysis. The researcher carried out the interpretation process heuristically and hermeneutically.…”
Section: Ethnography and Ethnographermentioning
confidence: 99%